2012
DOI: 10.4172/2155-9880.s2-005
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Alpha-Amylase Activity, a New Biomarker in Heart Failure?

Abstract: Abstractsystem. Autonomic imbalance is associated to several diseases, one of which is heart failure, and the aim of the Methods: In this pilot study, 48 elderly men (range 59-89 years), 24 patients with established chronic heart failure in NYHA class I to III, and 24 controls were included. In all participants, saliva was collected for three consecutive days at three time points (at awakening, 30 minutes later and in the late afternoon), and blood was sampled for analysis of NT-proBNP. Results:levels with art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…socio-demographic, clinical examination, medical condition, lab tests, medication intake, phenotypic data, sensor data) along with machine learning techniques are presented in [24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]49]. Recent studies have identified certain biomarkers which strongly correlate with the HF severity, progression and mortality [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81], while the progress in analytical chemistry and biosensor development allowed their detection in saliva and breath [82][83][84][85] with prominent merits due to the easy and non-invasive sample collection. The Event prediction module aims to inform the experts about the possible presence of adverse events (relapses and mortality): (i) by introducing saliva and breath biomarkers into the adverse event prediction process, (ii) based on a machine le...…”
Section: Event Prediction Modulementioning
confidence: 99%
“…socio-demographic, clinical examination, medical condition, lab tests, medication intake, phenotypic data, sensor data) along with machine learning techniques are presented in [24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]49]. Recent studies have identified certain biomarkers which strongly correlate with the HF severity, progression and mortality [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81], while the progress in analytical chemistry and biosensor development allowed their detection in saliva and breath [82][83][84][85] with prominent merits due to the easy and non-invasive sample collection. The Event prediction module aims to inform the experts about the possible presence of adverse events (relapses and mortality): (i) by introducing saliva and breath biomarkers into the adverse event prediction process, (ii) based on a machine le...…”
Section: Event Prediction Modulementioning
confidence: 99%
“…The last years' studies have revealed the strong correlation of saliva and breath biomarkers with HF severity, progression and mortality through statistical analysis methods [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…a-Amylase is a new biomarker for assessing the activity of the sympathetic nervous system and has been recently proved to be a prominent candidate for HF [6,7]. Cortisol is known to affect cardiovascular risk factors, such as hypertension that in turn influence survival.…”
mentioning
confidence: 99%